2017
DOI: 10.1093/ejcts/ezx442
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic surgery yields better outcomes than thoracotomy for anatomical lung resection in Brazil: a propensity score-matching analysis using the Brazilian Society of Thoracic Surgery database†

Abstract: In Brazil, the rate of complications associated with minimally invasive surgery (VATS) for anatomical lung resection is significantly lower than that of conventional OT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…According to the Brazilian Thoracic Surgery database, between August 2015 and December 2016, 52% of patients with lung cancer underwent minimally invasive anatomical lung resection. 5 This number is superior to those reported by the Society of Thoracic Surgery and the European Society of Thoracic Surgeons. Recently, robotic-assisted thoracic surgery was also adopted.…”
Section: Lung Cancer Surgerymentioning
confidence: 65%
See 1 more Smart Citation
“…According to the Brazilian Thoracic Surgery database, between August 2015 and December 2016, 52% of patients with lung cancer underwent minimally invasive anatomical lung resection. 5 This number is superior to those reported by the Society of Thoracic Surgery and the European Society of Thoracic Surgeons. Recently, robotic-assisted thoracic surgery was also adopted.…”
Section: Lung Cancer Surgerymentioning
confidence: 65%
“…6 Lobectomy is the surgical procedure performed most frequently. 5 Figure 1. Incidence (age-adjusted, per 100,000 inhabitants) and absolute number of new cases of lung cancer in Brazil according to geographic region and sex, estimated for the year of 2018.…”
Section: Lung Cancer Surgerymentioning
confidence: 99%
“…This is a clear advance over the rates reported in studies previously conducted in Brazil. The analysis performed by Tsukazan et al, 3 using the database of the Sociedade Brasileira de Cirurgia Torácica (SBCT, Brazilian Society of Thoracic Surgery), compared patients submitted to pulmonary resection by thoracotomy and those submitted to pulmonary resection by video-assisted thoracoscopic surgery. The complication rate in the thoracotomy group was 30.1%, compared with 21.8% in the video-assisted thoracoscopic surgery group.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Several studies have been published and confirmed the role of video-assisted thoracoscopic surgery in complex resections such as lobectomies and pneumonectomies. 3 , 4 Recently, robotic surgery has emerged as an alternative to conventional video-assisted thoracoscopic surgery, because it has the advantage of increasing the amplitude and precision of intracavitary maneuvers and movements, as well as improving visualization through three-dimensional imaging. 1 The use of robotics in thoracic surgery has been established in studies that demonstrated its feasibility, especially for mediastinal tumors and pulmonary resections, such as pulmonary lobectomy and segmentectomies.…”
Section: Introductionmentioning
confidence: 99%
“…[5] A study that analyzes patients undergoing lung resection elucidates that after propensity score matching, the major cardiopulmonary complication rate and overall complication rate in patients receiving VATS are reduced compared with patients who receive open thoracotomy. [17] A retrospective cohort study reports that the in-hospital mortality rate is markedly declined in patients with various lung diseases treated by VATS compared with that in patients treated by open thoracotomy. [18] These prior studies suggest that VATS may be more tolerable in patients with lung diseases including lung cancer than open thoracotomy.…”
Section: Discussionmentioning
confidence: 99%